Penyelenggaraan Pelayanan Publik yang Inovatif di Masa Pandemi Covid-19 - I Wayan Sutrisna (Universitas Mahendradatta Denpasar, 2021)
The pandemic caused by the Corona Virus Diseases 2019 (Covid-19) outbreak has had a very significant impact on human life. This epidemic not only caused a health crisis but also had an impact on the economy and the pattern of human life. The policy on social distancing in Indonesia has changed the pattern of public services into services with an online system. The online service model makes people who are not accustomed to using internet infrastructure experience obstacles in accessing the services they need.Changes in service models as a result of the Covid-19 outbreak require the community and government to be able to adapt to a new life pattern or new normal. During the new normal period, the implementation of public services is carried out through restrictions on social interaction by implementing health protocols to prevent the transmission of Covid-19. The bureaucracy must be able to produce innovation and creativity to make it easier for the community to obtain services so that the Covid-19 outbreak does not become a barrier for the bureaucracy in carrying out its main function as a public servant.Online-based service innovations that are easily accessible and easily understood by the public will be able to give confidence to the public that the Covid-19 pandemic is not an obstacle in obtaining public services. The purpose of this paper is to examine the implementation of innovative public services during the Covid-19 pandemic using a literacy study approach.